The Integration of Selober Traditional Music Within the song “Hakikat Sebuah Cinta” by Dr. Azam Dungun - Lalu Ahmad Alfian Bakti; Mohd Azam Sulong; Affendi Ramli (TAMUMATRA, 2024)
This study aims to explore the integration of traditional Lombok music, particularly the "Selober," into modern music through a unique composition titled *Lagu Hakikat Cinta* by Prof. Madya Azam Sulong. Employing a practical-based research design supported by document analysis, this project is structured into two main phases to achieve a coherent blend of traditional and contemporary elements. In the initial phase, the distinctive sounds of the Selober instrument were recorded and inputted into the digital audio workstation software *Sample One* to preserve its authentic timbre. Following this, in the second phase, the Selober sound was transformed and layered into four distinct tracks: Track Selober Transpose-12, Track Selober Delay, Track Selober Reverse, and Track Selober Snare. Each track reflects a different aspect of musical adaptation, allowing the traditional tones to harmonize with modern music elements. This method enabled the creation of a dynamic fusion, merging Selober’s traditional tones with digital sound effects, resulting in a distinctive piece that embodies cultural heritage within a modern musical framework. The final output, available in mp3 format, highlights the potential of digital technology in revitalizing traditional music and underscores its adaptability within contemporary musical landscapes.